Analisis determinasi tingkat kemiskinan di kabupaten/kota Provinsi Jambi - Rekha Alfionika; Yulmardi Yulmardi; Hardiani Hardiani (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2021)
This study aims to: 1) To analyze economic growth, unemployment rates, education levels, labor force participation rates (TPAK) and poverty rates in Jambi Province districts / cities in 2013-2018. 2) To analyze the effect of economic growth, unemployment rate, education level and labor force participation rate (TPAK) on poverty levels in Jambi Province in 2013-2018. Based on the results of panel data regression, it can be concluded that economic growth, unemployment rate, education level and TPAK together have a significant effect on poverty levels in districts / cities in Jambi Province. Partially, the variable of economic growth and the level of education have a significant and negative effect on the level of poverty, while the variable unemployment rate and the level of labor force participation do not significantly influence the level of poverty in the districts / cities in Jambi Province.